HISTOPATHOLOGICAL OF STRIPED CATFISH (Pangasianodon hypophthalmus) REARED IN DIFFERENT SALINITIES - Riswan, M; Syawal, Henni; Tang, Usman M; Effendi, Irwan; Kurniawan, Ronal; Wahyuni, Sri; Putri, Mega Novia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study aimed to discover the effects of different salinities on histopathological Pangasianodon hypophthalmus. The method used is experimental by applying a completely randomized design (CRD) with four treatments: salinity 0 ppt, salinity 5 ppt, salinity 7 ppt, and salinity 9 ppt. The fish specimen is 8-10 cm in length and weighs 5 g. It was raised in a 54 L tank containing 40 L of water at a density of 2 fish 1 L-1 and kept for 45 days. Feed with commercial pellet 3 times a day in satiation. The results showed histopathological changes in gills and kidneys occurred at a salinity of 9 ppt. Chloride cell hypertrophy and secondary lamella bend in the gill organs, while the kidneys have acute tubular necrosis. Meanwhile, a salinity of 7 ppt resulted in abnormalities in the kidney organs with hemorrhage. It can be concluded that a salinity of 5 ppt indicates a safe salinity condition for the maintenance of striped catfish.